2006
DOI: 10.1002/ejic.200600570
|View full text |Cite
|
Sign up to set email alerts
|

Oxalato‐Bridged Dinuclear Copper(II) Complexes of N‐Alkylated Derivatives of 1,4,7‐Triazacyclononane: Synthesis, X‐ray Crystal Structures and Magnetic Properties

Abstract: The synthesis, X-ray crystal structure and magnetic properties of two oxalato-bridged dinuclear Cu II complexes, [LCu(µ-ox)Cu-L](ClO 4 ) 2 , where ox = oxalate and L = 1,4,7-trimethyl-1,4,7-triazacyclononane (Me 3 tacn) or 1-benzyl-4,7-dimethyl-1,4,7-triazacyclononane (BzMe 2 tacn) are reported, as well as the X-ray crystal structure of the mononuclear complex, [Cu(Me 3 tacn)(OH 2 ) 2 ](ClO 4 ) 2 , which features an extended H-bonding network between the ligand and the perchlorate counterions. The crystal stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In this kind of system, special attention has been addressed to coordination architectures that include multiatomic bridging ligands (MABLs). Thus, MABLs such as oxalate azide or 2,2′-bipyrimidine (bpym) have been extensively used in magneto-structural studies because of their remarkable ability in mediating magnetic interactions between paramagnetic centers as well as the variety of dimensionalities (from both structural and magnetic points of view) and topologies that they can originate when adopting different coordination modes. Despite the variety of bpym-including ternary systems characterized, those that include carboxylate groups are relatively uncommon.…”
Section: Introductionmentioning
confidence: 99%
“…In this kind of system, special attention has been addressed to coordination architectures that include multiatomic bridging ligands (MABLs). Thus, MABLs such as oxalate azide or 2,2′-bipyrimidine (bpym) have been extensively used in magneto-structural studies because of their remarkable ability in mediating magnetic interactions between paramagnetic centers as well as the variety of dimensionalities (from both structural and magnetic points of view) and topologies that they can originate when adopting different coordination modes. Despite the variety of bpym-including ternary systems characterized, those that include carboxylate groups are relatively uncommon.…”
Section: Introductionmentioning
confidence: 99%
“…Adapted from Refs. and with permission. Copyright 2003, Royal Society of Chemistry and 2006, John Wiley and Sons.…”
Section: Structural Models For Metallobiositesmentioning
confidence: 83%
“…Systematic variation of the intramolecular Cu–Cu distance in these binuclear models also showed that the electronic interaction between the Cu II centres diminishes with increasing separation. The complexes studied range from ones that display moderate antiferromagnetic coupling, for example, Cu II 2 – 12 ( J =−86 cm −1 ), which features an endogenous alkoxo‐bridged pair of Cu II centres separated by approximately 3.6 Å, through to complexes exhibiting strong antiferromagnetic interaction between the Cu II centres, for example, Cu II 2 – 13 ( J ≈−150 cm −1 ), which is an oxalato‐bridged binuclear Cu II complex with a large Cu–Cu separation (≈5.2 Å; Figure ). This distance is further reduced (≈3.80 Å) in Cu II 2 – 14 , a cis ‐Cu II 2 (μ‐η 1 :η 1 −O 2 ) complex of pyrazole‐bridged TACN (Figure ), reported by Meyer and co‐workers .…”
Section: Structural Models For Metallobiositesmentioning
confidence: 99%
“…A major focus of our work has been on new tacn-based ligands capable of generating structural models for copper protein active sites. The metal centers within copper proteins generally reside in sites generated by four or five metal-coordinating residues, with the coordination sphere completed by aqua ligands and/or substrate donor atoms. For example, histidine residues bind to copper ions in the mono-, di-, or trinuclear Cu­(II) sites of hemocyanin, ceruloplasmin, dicopper dismutase, galactose oxidase, catechol oxidase, and quercetin 2,3-dioxygenase .…”
Section: Structural Metallobiosite Modelsmentioning
confidence: 99%